A Comparison of Three Types of “Vineyard Management” and Their Effects on the Structure of Plasmopara viticola Populations and Epidemic Dynamics of Grape Downy Mildew - Yu, Shuyi; Li, Baihong; Guan, Tianshu; Liu, Li; Wang, Hui; Liu, Changyuan; Zang, Chaoqun; Huang, Yuqian; Liang, Chunhao (Plants (Basel), 2022)
Grape downy mildew (GDM) is a destructive grapevine disease caused by Plasmopara viticola that occurs worldwide. In this study, we determined the characteristics of GDM epidemics and the grapevine canopy micro-climate in open-field, fungicide-spray, and rain-shelter plots during two constitutive years (2016 and 2017). It was found that rain shelter can significantly delay the disease occurrence by 28 and 21 days, reduce the epidemic phase by 28 and 21 days, and decrease the final disease index by 82% and 83%. Furthermore, it can block precipitation, reduce the relative humidity by 11% and 8%, and reduce the leaf wetness duration by 85% and 76% compared with open-field cultivation. A total of 3861, 783, and 1145 lesions were collected from the open-field, fungicide-managed, and rain-shelter plots, respectively, for analyses of the genetic diversity, population differentiation, and epidemic mode with seven microsatellite markers. In terms of genetic diversity, the Nei’s diversity index ranged from 0.569 to 0.680 and Shannon’s information index ranged from 0.958 to 1.226, showing high levels of diversity across populations. Similar to fungicide management, a rain shelter can significantly reduce the population’s genetic diversity. Low pairwise FST values (0.003–0.047) and high gene flow (Nm = 1.548–20.699) were observed among the three populations each year. In addition, most of the genetic variation occurred within populations. The epidemic mode of GDM in the open-field, fungicide-managed, and rain-shelter cultivation showed moderate, low, and high levels of clonality, respectively, in the case study.